Medieval History in the Modern Classroom: Using Project-Based Learning to Engage Today's Learners - Sobehrad, Lane J. (2022)
Teaching medieval history should engage students in the real work of professional medievalists. However, many undergraduate courses rely on instructional strategies that only engage students in rote retention of medieval 'stuff' and unsupported writing assignments. With trends in the USA and elsewhere showing declining undergraduate enrollment in the humanities and an increasing number of questions from university administrators regarding the utility of the liberal arts, historians need to reassess how they teach. Project-based learning (PBL) is one approach that may help medieval history instructors offer coursework that is more engaging for today's undergraduate students and provide administrators a clearer picture of the utility of studying the past. The pedagogy of PBL actively engages students in projects reflective of the real work being done by medievalists, allowing instructors to move beyond the traditional narrative found in many undergraduate survey courses. This book provides an overview of PBL theory, methods for incorporating PBL into an undergraduate medieval history course, instructional strategies, scalable assessment formats, and other resources useful for any history classroom.